Ecological adaptation in cod and herring and possible consequences of future climate change in the Baltic Sea - Andersson, Leif; André, Carl; Johannesson, Kerstin; Pettersson, Mats (Frontiers in Marine Science, 2023)
The Atlantic herring and Atlantic cod are two marine fish species that have successfully adapted to the brackish Baltic Sea, and the former is able to spawn in near-freshwater conditions in the inner Gulf of Bothnia. Here, we review the state of current knowledge concerning ecological adaptation in the two species and make an attempt to predict how they will be able to cope with future climate change. Previous whole genome sequencing studies in Atlantic herring have revealed hundreds of genetic loci underlying ecological adaptation, including several loci that show very strong associations to variation in salinity and temperature. These results suggest the existence of standing genetic variation available for adaptation to a changing environment. However, although Atlantic herring probably has the genetic potential to adapt, its future status also depends on how climate change will affect plankton production and competing species, such as sprat and three-spined stickleback. In cod, the situation is challenging, as there is only one true Baltic population, spawning east of Bornholm and then dispersing towards the east and north. This Baltic cod population is threatened by overfishing, low oxygen levels in benthic waters and generally bad physiological condition of individual fish, in addition to being completely isolated from gene flow from nearby cod populations at the entrance of the Baltic Sea.